The Genealogy of Turkish Transnational Movement in Indonesia - Purwaningtyas, Dhita Ayomi; Rimapradesi, Yulia; Hutama, Achmad Reza (UI Scholars Hub, 2024)
The majority of transnational Islamic groups in Indonesia come from the Middle East, which emphasizes various missions, such as purification and political ideology, and some others are Salafi-jihadist. Turkish transnational movement's mission mostly is religious da'wah through culture and education without spreading any political ideology, including the Nur Movement, the students of Bediuzzaman Said Nursi. Amid suspicions about the increasingly widespread cases of extremism and radicalism in Indonesia by transnational groups that have brought the antithesis of Indonesian Islam, the Nur Movement has been able to enter and develop. This article analyzes the genealogy and distribution of the Nur Movement and its impact on the coloring of Islam in Indonesia. This type of research is qualitative, using literature data collection methods, interviews, and observations conducted in 2023. Based on the analysis, the genealogy of the Nur Movement is the interest of Indonesian academics in studying the Risale-i Nur and the opportunities that the Nur Movement has from the flexibility of Indonesian Islam. The Nur Movement can develop in Indonesia because they collaborate with the locals, being adaptive and inclusive.